KONSEP TANGGUNG JAWAB EMMANUEL LEVINAS DAN IMPLIKASINYA BAGI KEBERAGAMAAN INDONESIA - Kamilus Pati Doren (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: "Am I my brother's guard?" This question becomes a reflection of individuals as social being who meet with other people every day in their differences. This question inspires the conscience of each person to take the right attitude when dealing with others. And the attitude referred to here is responsibility in the concept of levinas, which is different from everyday understanding. This thought was then tried to collide with diversity in Indonesia, especially the attitude of religious people when dealing with adherents of other religions. so that the moment of meeting with others truly becomes an ethical moment towards meeting, based on this attitude of responsibility. Based on library data, the author tries to describe the concept of levinas responsibility so that ultimately every difference can be seen as a gift and shared wealth. Through reflection on the unique concept of the responsibility of levinas, the authors put it as a foundation for the relations of religious life and Indonesian society, which often experience clashes due to pluralistic reasons. It is very appropriate, if Levinas's responsibilities are implied into the lives of our people because also the essence of Levinas's thinking actually has a strong foundation in our country's philosophy. KEYWORDS:  responsibility, plurality, religion, others, le visage, meeting